Sports Therapy : Theoretical and practical thoughts and considerations - Briggs, James; Northern Institute of Massage (Chichester : Corpus, 2001)
With increased interest since the mid 1980s in the science of sport, this text overviews the role of the sports therapist. It provides both a theoretical and practical foundation on which to build further knowledge, skills and expertise.
Published in collaboration with the Northern Institute of Massage.
Includes bibliographical references and index.
Keywords: Sports physical therapy; Health and Fitness